Initial Recognition and Prophecy of Diabetic Nephropathy in Type I Diabetes in a Sample of Iraqi Patients - Akram, Wijdan (AL-Kindy College Medical Journal, 2012)
Back ground: Diabetic nephropathy is rapidly becoming the leading cause of end-stage renal disease (ESRD). The onset and course of DN can be ameliorated to a very significant degree if intervention institutes at a point very early in the course of the development of this complication. Objective: The aim of this study was to characterize risk factors associated with nephropathy in type I diabetes and construct a module for early prediction of diabetic nephropathy (DN) by analyzing their risk factors. Methods: Case control design of 400 patients with type I diabetes mellitus (IDDM), aged 19-45 years. The cases were 200 diabetic patients with overt protein urea while the controls were 200 diabetic patients with no protein urea or micro-albumin urea. Results: concurrent occurrence of retinopathy and nephropathy was the main predictors for nephropathy in type I DM patients. Disease duration more than 10 years, uncontrolled hyperglycemia, age more than 30 years and presence of hypertension were the other predictors respectively. Gender and hypercholestremia showed no predictive value in occurrence of DN.